PHYSIOLOGICAL CHARACTERISTICS OF SINGLE JUNIOR BADMINTON MATCH PLAY - RIZKY AKBARI, MOCHAMAD
Background: Measurement of cardiovascular, metabolic, and respiratory were fundamental in assessing athletes' performance. It’s were important for coaches to obtain supporting data in developing training methods. At the level of junior badminton athletes, research related to physiological and match characteristics is still quite limited. This study aims to describe the physiological and match characteristics of single junior badminton athletes in a match simulation. Methods: This study used an observational method with a quantitative descriptive design. The research subjects were elite junior badminton athletes with 13 athletes consisting of 7 men and 6 women. Each subject carried out two stages of research. The first stage consists of anthropometric measurements and VO2Max. The second stage consists of measuring physiological characteristics in a match simulation using a portable metabolic device. In addition, the characteristics of the match were also analyzed through video recordings during the match simulation. Results: Based on statistical analysis Two-Sample T-Test stated that there was a significant difference in VO2 39.8 ml.min -1 .kg -1 (men) and 27.6 ml.min -1 .kg -1 (women) (p=0.001) or 78.5% VO2Max (men) and 60.4 %VO2Max (women) (p=0.006). There was no difference in HR during the match simulation, 162.1 bpm (men) 160.8 bpm (women) (p>0.05). Two-Sample T-Test stated that there were differences in blood lactate 6.94 mmol/L (men) 5.58 mmol/L (women) (p=0.019). The characteristics of the match in the men single were more dominant to use drive shot (p<0.05) while women were more dominant to use clear shot (p<0.05). The rally time when playing in the men and women singles is around 7 seconds and the rest time for each rally that played is around 10-12 seconds. Conclusions: This study reveals, that badminton is an intermittent sport with moderate-high intensity, with a shorter rally time than the rest time in each rally. Men single have a higher intensity characteristic than women. The men single are dominant in aggressive shot-like drives. While women single more often use elongated shots such as clear. Through this study, recommendations for training design with the method of high-intensity interval training to improve aerobic and anaerobic alactic acid systems.